Electrochemistry of the organic molecule methylene blue - Colleran, John (Trinity College (Dublin, Ireland). School of Chemistry, 2008)
The first Chapter deals with the general information about chemically modified electrodes, what they are, the development of fabrication techniques, and relevant applications of modified electrodes. This is followed by some background on the redox polymer, polymethylene blue, and closes with a description of magnetoelectrochemistry. in Chapter 2 the experimental procedures and theory used in this body of research are dealt with in good detail. The first part of Chapter 3 describes the solution phase electrochemistry of the organic phenothiazine dye, methylene blue, at a glassy carbon electrode. The effect that dimerisation has on the diffusion coefficients and electron transfer kinetics, is explored. Adsorption was observed at the glassy carbon electrode and an adsorption isotherm constructed. The maximum surface coverage for a MB monolayer was extracted from the isotherm data. The solid phase electrochemistry of MB was also investigated via electropolymerisation of the monomer onto the glassy carbon electrode. The charge carried by the polymer films was examined as a function of initial concentration of the monomeric solution and of the number of cyclic voltammetric polymer growth cycles applied. A value for the diffusional charge transfer coefficient was estimated using cyclic voltammetry. EQCM was employed to quantify the movement of counterions through the film and a stoichiometric expression for this redox process was proposed.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin